[Fortunato shared her experiences on the translation process of Ferdinand Blumentritt] - Fortunato, Teresita F. (Animo Repository, 1998)
Teresita Fortunato of the Philippine Languages Dept. shared with the Lasallian community her experiences during the translation process of Harry Sichrovsky's German book, Ferdinand Blumentritt: an Austrian Life for the Philippines. The lecture, Salin: Sa Pagitan ng Dalawang Kahulugan, Sa Pagitan ng Dalawang Kasaysayan was part of the Rufino Alejandro Lecture Series.